Return Migration Decisions : A Study on Highly Skilled Chinese in Japan - Achenbach, Ruth (Life Course Research, 2017)
Ruth Achenbach develops a model of individual return migration decision making, which examines both the process and the decisive factors in return migration decision making of Chinese highly skilled workers and students in Japan. She proposes to answer a question yet insufficiently explained by migration research: why do migrants deviate from their migration intentions and return sooner or later than planned, or not at all? Her study integrates factors from the spheres of career, family and lifestyle, and redefines stages in long-term decision-making processes, thereby contributing to decision and migration theory. She analyzes migrants' shifting priorities over the course of migration, including a perspective on life course and on the impact of the triple catastrophe of March 11, 2011. Contents Return Migration Decision Making: Theoretical Considerations Chinese Migration to Japan: Then and Now A Conceptualization of (Locational) Decision-Making Processes Impact of Career, Family and Lifestyle Factors on Migrants' Locational Decisions Target Groups Researchers and students of Sociology, Migration, Decision Research, and Political Science Practitioners of Regional Studies Japan / China The Author Ruth Achenbach is Academic Coordinator at the Interdisciplinary Centre for East Asian Studies (IZO) at Goethe University Frankfurt. Her research focuses on migration in East Asia with a focus on Japan. .